On the net radiation method for heat transfer - de Micco, Carla (2003)
A simplifying approach for calculating the radiant energy is achieved by introducing the concept of net transmittance, resulting in a novel variation of the net radiation method that provides an easy way for solving a variety of situations. In particular, a closed form for the net radiation between two grey plates through a radiation shield formed by a series of partially transparent partially reflecting partially absorbing plates is found. In addition, the method is generalized to cylindrical and spherical geometries.